Czas, ulice i lustra — „Cléo od piątej do siódmej” Agnès Vardy - Norbert Pilarz (Studia Filmoznawcze)
This article focuses on the analysis of Agnès Varda’s Cléo from 5 to 7, mainly examining three elements—time, places and the motif of mirrors. The text discusses relations between these layers and how these problems affect the main character. An important element of the text is also confronting the film’s reception. The analysis also focuses on the film’s relations with the poetic of the French New Wave (similar aesthetics, but also many differences with the works of e.g. Godard and Truffaut).